Students’ Perception towards Online-Class during COVID-19 Pandemic - Mahat, Dipak (International Research Journal of MMC, 2021)
Effect of COVID-19 on educational institution has interrupted the traditional method of teaching and learning which ultimately created the demand of online class. In this background, study aim was to find out the perception of students towards online-class during COVID-19 pandemic. The study was based on descriptive research design. The study was carried out by using the structured questionnaire survey, and self-administered online Google firm was developed to collect the data. The data were collected from 109 students of two colleges; one public and one private college. The reliability test of collected data was checked by calculating the Cronbach’s Alpha value. Frequency, percentage, and mean was used to analyze the data. Finding of the study revealed that 81.7% students adopted online class first time in their learning career. However, majority of respondents felt confident to use online-class function and adopt content. Similarly, 58.1% respondents reported that they faced the technical problem during Online-class, more than 59% respondents believed that online class was one of the easiest platforms to share the knowledge and collect the required information. Most of the respondents intended to use online-class platform to enhance their learning and communication skill. One of the main benefits of online class was that it has saved the students from risk of transmission of COVID-19 and contributed to the regularity of teaching and learning of college. Considering such critical time, colleges should provide the adequate knowledge of Information Technology (IT) to their students and teachers to enhance their technical skill.